How we accidentally built an AI-powered writing app for researchers - ASTBURY, Marc (Institutional Knowledge at Singapore Management University, 2024)
In this session, Marc will delve into the research, insights, and other behind-the-scenes efforts that go into building Jenni AI, an academic writing app with 3m+ users. Participants will also have the opportunity to engage in a guided demo to experience the app firsthand.